La defectuosa construcción del lawfare como mito en Brasil y Argentina: entre la pesadilla y el noble sueño de la neutralidad política en la justicia penal - Laise, Luciano D. (2023)
The notoriety that criminal proceedings against Latin-American political figures have acquired led some to argue that such proceedings constitute a perverse attack against popular leaders who oppose the neoliberal agendas of the global north. Before this issue, in this article I intend to systematically reconstruct the specialized literature on the concept of lawfare. Then I will outline both mythical and fallacious nature of many of the explanations and implications for so-called lawfare. Since those criticisms, I will highlight two relevant topics: (i) the necessary respect for the basic procedural guarantees for any person who is accused of serious crimes against public administration, and (ii) the inevitable political dimension of legal interpretation.